Exploitation of Women and Children in Nepal: In the Name of Travel, Tourism and Marriage. Issue 2 (December 2017) - Koirala, Anuradha; Khadka, Bishwo Ram
Trafficking in Nepal and in its associated South Asian Association for Regional Cooperation (SAARC) region is more heavily entrenched than a decade ago. Nepal is no longer just a source country, but has become a transit and destination country as well. Sex tourism targeting minors has increased. Legal loopholes in Nepali law provide spaces for increasing paedophilia by tourists. Fake marriages have become a common method of trafficking. Trafficking is still primarily for prostitution, but there is an increase in trafficking for domestic servitude, construction work, cheap labor, slavery and organ harvesting. Policy responses are confused due to political instability and a lack of coordination among different departments.